Mechanical and durability properties of modified High-Performance mortar by using cenospheres and Nano-Silica. (2nd January 2023) - Najeeb, Zeyad; Mosaberpanah, Mohammad Ali
Highlights: High-performance mortar was prepared with cenospheres and nano-silica. The performance was evaluated based on mechanical and durability properties. Nano-silica produced a denser and compacted structure. Incorporating 10% of cenospheres with nano-silica enhanced overall performance. Abstract: The cement industries including excavating raw materials, burning processes, and transportation are responsible for 7% of worldwide carbon dioxide emissions due to rapid development in construction and urbanisation increased consumption of cement in the last few decades noticeably followed by environmental pollution. The incorporation of Supplementary Cementitious Materials (SCMs) like fly ash, silica fume, and granulated blast furnace slag in cement-based composites showed to be a remarkable technique to reduce cement consumption while enhancing its strength and durability. This study aimed to utilise Cenospheres (CS) and Nano-Silica (NS) to produce sustainable high-performance mortar based on the design of the experiment concept by incorporating (0–20) % of CS as a cement substitute and (0–2) % of NS as an additive admixture at a fixed W/B of 0.35. The performance of CS and NS in the mortar was evaluated based on mechanical properties (compressive and flexural strength), durability properties (water absorption, fire resistance, sulfuric acid attack, drying shrinkage), and microstructure. A denser and compacted structure was attained by the addition of (1–2) % of NS which improved the compressive and flexural strength of the mortar by (8–13) % and (23–26) % respectively, whereas employing 10 % of CS in the mortar reduced compressive strength as compared to the control mixture. However, CS particles increased the absorbance capacity of bending energy resulting in enhancing flexural strength by 15%. NS/CS mixtures showed excellent resistance to high temperatures and sulfuric acid by improving residual compressive strength. NS particles increased the drying shrinkage among all ages due to the high pozzolanic rate. In contrast, using 10% CS reduced the drying shrinkage by 10% as compared to the control mixture. The SEM analysis revealed that NS produced a denser and more compacted structure resulting in reduced water absorption capacity of the mortar as compared to CS mixtures. It was concluded that incorporating 10% of CS with 1% of NS in the mortar was the most adequate utilisation level to improve the stated above properties.